BIODEGRADATION OF ORGANIC MATTER IN CAI RIVER MOUTH - NHA TRANG - Minh Thụ, Phan; My Nga, Ton Nu (Vietnam Journal of Marine Science and Technology, 2018)
To assess characteristics of organic matter biodegradation of waters at Cai river mouth - Nha Trang, the maximum ratio, half-saturation constant, decay ratio constant and half-time of organic matter biodegradation were estimated. Based on the experiment results with water at Cai mouth in dry season of 2013 & 2015 at high tide and low tide, and solution of Michaelis & Menten function in the case of BODn by least squares method, the paper indicated that organic matter biodegradation presented the local and specific characteristics and by slightly impacted by tidal systems in river mouth. The organic matter in Cai mouth was degraded easily and its origin was mainly from spontaneous waste or domestic waste.